A study of phenotypic and genetic aspects of reproduction rate in the Tygerhoek Merino flock - Cloete, S. W. P. (Schalk Willem Petrus van der Merwe) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Agric.) -- University of Stellenbosch, 1986..